Evaluation of Prescriptions and Use of Intravenous Pantoprazole in General Wards and Intensive Care Unit of Shahid Sadoughi Hospital in Yazd - Seyed-Mojtaba Sohrevardi; Alireza Vahidi; Mohammad-Hossein Mosadegh; Arefeh Dehghani-Tafti; Anita Dadollahi (Research Center for Rational Use of Drugs (RCRUD), 2016)
Background: Proton pump inhibitors (PPIs) are currently the most effective agents for acid related disorders. However, studies show that 25-75% of patients receiving intravenous Pantoprazole had no appropriate justification, indicating high rate of inappropriate prescribing in hospitals. The aim of this study is to examine the appropriate use of intravenous Pantoprazole in accordance with guidelines at Shahid Sadoughi hospital. Methods: From January to April 2015, sample of 100 prescriptions who received Intravenous (IV) Pantoprazole were collected with observational and sectional model in Intensive care unit (ICU) and general wards of "Shahid Sadoughi" Hospital of Yazd, Iran. Clinical data from patient records are obtained and these data were mapped to establish clinical criteria and appropriate use of Intravenous Pantoprazole. Results: The majority (63%) of Intravenous Pantoprazole prescriptions were deemed inappropriate in terms of either indication for use, dose or duration of therapy. 51.5% of the patients were above 55 years old. Endoscopy did not performed in most of the Non UGIB (Non upper gastrointestinal bleeding) cases. Most Intravenous Pantoprazole prescriptions were ordered by junior doctors (Intern), and again this group were significantly less likely to prescribe the drug for appropriate reasons when compared with more experienced clinicians. Conclusion: This study suggests that the majority of IV PPI prescriptions in our hospital are inappropriate. Awareness of the result of this article through medical staff could result in more judicious use of intravenous pantoprazole and dose optimization. Physicians and pharmacists can work together to create solutions to inappropriate drug use.